The analysis of occupational accidents among the healthcare staffs - Özenir, Songül; Ünver, Vesile (The European Research Journal, 2020)
Objectives: The aim of the study is to identify the attitudes of healthcare professionals towards the potential occupational accidents and the safe use of sharp instruments in their work environment. Methods: The study was carried out between February 2017 and March 2017 with the participation of 173 health care personnel. The data collection forms consist of two parts, “Questionnaire about the occupational accidents that the participants might experience” and the“Attitude scale about the safe use of sharp objects and instruments by the participants”. Results: The number of injuries they experienced in the same period varied between 1 and 12 and the mean injury cases were found to be 2.76 ± 2.59. The total score of the participants from the Attitude scale was found to vary between 68 and 112, with a mean total score of 81.65 ± 7.03. Conclusions: The participants of the study are subject to serious occupational accidents and occupations risks which may negatively affect their health.